NILAI-NILAI PENDIDIKAN TOLERANSI RASULULLAH DENGAN NON MUSLIM - Ahmad Hifdzil Haq; Suprapno Suprapno; Adisel Adisel; Moch Iqbal; Riswanto Riswanto (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
Tolerance is a value that is very familiar to us as Indonesian citizens who are multicultural, with various ethnicities, cultures, languages and religions. But not infrequently we as Muslims have not been able to place its meaning proportionally. This paper aims to reveal how the Prophet taught tolerance towards non-Muslims. The method used in this article is the library method. The results presented are that Islamic tolerance lies in the concept of "tasamuh", uniquely, Islamic tolerance is carried out to all humans regardless of religion. The concept of tasamuh is also very tied to other basic concepts in the Qur'an. When we talk about tasamuh, we cannot escape the concepts of al-Rahmah, al-Adl-Qist, al-Ihsan, al-Amanah, al-Salam and al-Tawhid. All of these terminology are the basic concepts that bind the tasamuh concept. So, if the West wants to fuse all truth in religions, Islam actually strengthens the concept of Tasamuh by tying it with al-Tawhid. By giving good examples and examples, the Prophet taught his companions how ideally to be tolerant, especially towards non-Muslims